Effects of the ethanol extract of the inner bark of Syderoxylum obtusifolium in the cyclophosphamide-induced cystitis in rats - Pereira, Denyson Santana (2013)
Bezerra, Daniel Pereira “Documento produzido em parceria ou por autor vinculado à Fiocruz, mas não consta à informação no documento”.